Unwritten rule : state-making through land reform in Cambodia - Beban, Alice, 1981- (Cornell series on land., 2021)
"This book investigates the importance of land in postconflict states through the study of a political campaign to develop land registration efforts inside agribusiness concessions in Cambodia"--